Access to Reproductive Health Services and Maternal Perceptions on Family Planning in an Indigenous Guatemalan Valley. (31st December 2018) - Lambert, Lauren Ashley; Hatcher, Jeremy Brittingham; Wang, Xinyu
Abstract : Objective. To identify reproductive health barriers and perceptions regarding family planning among mothers in ten rural communities of Guatemala. Methods. Data were collected from 85 women in a Nutrition Recuperation Project (NRP) conducted by a freestanding nonprofit clinic in Palajunoj Valley, Guatemala. All nonpregnant women participating in the NRP were eligible for enrollment in this study, and NRP staff members aided in their enrollment. Participants were interviewed and data were entered into a structured questionnaire. Data analysis was conducted using R version 1.1.456. Results. After asking participants if they believed fertility is higher on certain days, only 5 women (5.9%) correctly identified these days as occurring in the middle of the menstrual cycle. 35 women (41.2%) practiced some form of family planning, and 27 (31.8%) reported that they do not know of a place where they could obtain a contraceptive method. Conclusion. There is a lack of education regarding family planning methods in this valley, and the levels of contraception use are below average for rural Guatemala. These findings may implicate substantial health risks for women and children in the valley, and they support the pertinence of education-based interventions in the area of reproductive health behaviors.